2003
DOI: 10.1083/jcb.200301133
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 translates chemokine signals to integrin activation, cell polarization, and motility across vascular endothelium under flow

Abstract: Chemokines arrest circulating lymphocytes within the vasculature through the rapid up-regulation of leukocyte integrin adhesive activity, promoting subsequent lymphocyte transmigration. However, the key regulatory molecules regulating this process have remained elusive. Here, we demonstrate that Rap1 plays a pivotal role in chemokine-induced integrin activation and migration. Rap1 was activated by secondary lymphoid tissue chemokine (SLC; CCL21) and stromal-derived factor 1 (CXCL4) treatment in lymphocytes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
318
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(336 citation statements)
references
References 46 publications
15
318
3
Order By: Relevance
“…At the molecular level, we show that CRK proteins function to promote chemokine-dependent integrin activation by RAP1, a key event needed for adhesion to endothelial cells and subsequent diapedesis (27). Previous work has shown that CRK proteins signal through the RAP1 GEF C3G to regulate RAP1 activation (4,13,14,28).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…At the molecular level, we show that CRK proteins function to promote chemokine-dependent integrin activation by RAP1, a key event needed for adhesion to endothelial cells and subsequent diapedesis (27). Previous work has shown that CRK proteins signal through the RAP1 GEF C3G to regulate RAP1 activation (4,13,14,28).…”
Section: Discussionmentioning
confidence: 76%
“…We observed that in addition to playing a role in inside-out signaling pathways leading to integrin activation, CRK/CRKL Dko T cells polarized poorly in response to fibronectin ligation. This indicates that these proteins, like RAP1 (27,31), are also required for outside-in integrin signaling.…”
Section: Discussionmentioning
confidence: 98%
“…The ras-like small GTPase Rap1 has recently emerged as an important regulator of early integrin activation by chemokine signals (42)(43)(44). Its crucial role in LFA-1 triggering is also evident from the latest description of a human genetic defect, leukocyte adhesion deficiency (LAD-III) (44), in which the expression of the Rap1 GEF, CalDAG-GEF-1, is impaired (45).…”
Section: Discussionmentioning
confidence: 99%
“…Rap1 is known to stimulate integrin activation, cytoskeleton rearrangements, and cell polarization both in the presence and absence of a chemokine gradient. 42,43 We observed that Rap1a and Rap1b depletion abolished the migratory advantage of MEC1-CD38H cells. This indicates that Rap1 activity contributes to the increased migration and adhesion linked to CD38 expression.…”
Section: Discussionmentioning
confidence: 76%